2007
DOI: 10.1631/jzus.2007.b0853
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of a panel of gene expression in prostate cancer—with emphasis on NPY expression analysis

Abstract: Abstract:Objective: To investigate molecular alterations associating with prostate carcinoma progression and potentially provide information toward more accurate prognosis/diagnosis. Methods: A set of laser captured microdissected (LCM) specimens from 300 prostate cancer (PCa) patients undergoing radical prostatectomy (RP) were defined. Ten patients representing "aggressive" PCa, and 10 representing "non-aggressive" PCa were selected based on prostate-specific antigen (PSA) recurrence, Gleason score, pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…10 The role of NPY in human tumours is unclear. Several studies have indicated the existence of a correlation between NPY and cancer progression in tumours such as neuroblastoma, 11 prostate cancer, 12 non-Hodgkin lymphoma, 13 breast cancer, 14 Ewing sarcoma cells and intracranial tumours. 14 The latter study also demonstrated an association between NPY and decreased tumour growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…10 The role of NPY in human tumours is unclear. Several studies have indicated the existence of a correlation between NPY and cancer progression in tumours such as neuroblastoma, 11 prostate cancer, 12 non-Hodgkin lymphoma, 13 breast cancer, 14 Ewing sarcoma cells and intracranial tumours. 14 The latter study also demonstrated an association between NPY and decreased tumour growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the diffuse positivity of the neuroendocrine marker, NPY, observed in human ductular cholangiocarcinoma samples is supported by a number of studies. Indeed, Liu et al (33) have demonstrated higher expression of NPY in nonaggressive prostate epithelial tumors. Moreover, these observations about the nonconventional immunolocalization of neuroendocrine proteins are previously discussed in cholestasis and cholangiocarcinoma where the important role of GABA, chromogranin A, glycolipid A2-B4, S-100 protein, and neural cell adhesion molecule are demonstrated by us and other groups (17, 37, 46 -48), suggesting that the biliary epithelium is a significant target for the neuroendocrine system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inflammation, differences in gene expression patterns and genome instability are associated with cancer progression [18,19]. In PCa, one of the most studied gene mutations is the loss of phosphatatse and tensin homolog (PTEN).…”
Section: Introductionmentioning
confidence: 99%